2021
DOI: 10.3389/fphar.2021.583387
|View full text |Cite
|
Sign up to set email alerts
|

Plant Products as Inhibitors of Coronavirus 3CL Protease

Abstract: Background: The ongoing COVID-19 pandemic has created an alarming situation due to extensive loss of human lives and economy, posing enormous threat to global health security. Till date, no antiviral drug or vaccine against SARS-CoV-2 has reached the market, although a number of clinical trials are under way. The viral 3-chymotrypsin-like cysteine protease (3CLpro), playing pivotal roles in coronavirus replication and polyprotein processing, is essential for its life cycle. In fact, 3CLpro is already a proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 120 publications
(111 reference statements)
1
38
0
3
Order By: Relevance
“…Clinical trials of a few herbal compounds against SARS-CoV-2-3CL Pro aroused hope for plant-derived anti -SARS-CoV-2 drugs. Very recently, 3CL protease inhibitor NLC-001, a plant product administered orally as a dietary supplement, got US FDA approval [ 61 ].…”
Section: Some Herbal Medicine Used In Covid-19mentioning
confidence: 99%
“…Clinical trials of a few herbal compounds against SARS-CoV-2-3CL Pro aroused hope for plant-derived anti -SARS-CoV-2 drugs. Very recently, 3CL protease inhibitor NLC-001, a plant product administered orally as a dietary supplement, got US FDA approval [ 61 ].…”
Section: Some Herbal Medicine Used In Covid-19mentioning
confidence: 99%
“…The primary purpose of this manuscript is to disseminate some knowledge about necessary drugs which could be used subject to trial results. Previous studies mainly report terpenes [ 65 ], phytomedicine [ 66 ], extracts from spices [ 67 ], marine products [ 68 ], plants secondary metabolites and various other forms of drugs as potential candidates as SARS CoV-2 inhibitors [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urtica dioica agglutinin (UDA) an active compound derived from the Urtica dioica plant species which prevents the viral attachment to cell through binding with the glycoprotein of SARS-CoV virus [ 52 ]. Earlier study suggested that traditional Chinese medicinal (TCM) plans Scutellaria baicalensis Georgi, used globally as a broad spectrum antiviral compound, which also have the anti-Covid-19 3CL pro activity in in-vitro study [ 53 ]. Luteolin (flavonoid) and resveratrol (terpenoid) are extracted from Veronica linariifolia plants and strongly inhibited entry of coronavirus by interfering with spike protein and ACE2 receptor of SARS-CoV [ 53 , 54 ].…”
Section: The Common Class Of Antiviral Phytochemicals Derived From Traditional Herbsmentioning
confidence: 99%